Synthesis and Characterization of Tetradentate Complexes Type N2O2 From the Reaction of 2-Hydroxy -1, 2-Diphynel-Ethanone Oxime [H2L] With Mn II, Fe II, Co II, Ni II, Cu II and Hg II Ions - Numan, A.Th.; Alsalehe, E. I.; Aldulaimi, J. H. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
Tetradentate complexes type [M (HL) 2] were prepared from the reaction of 2-hydroxy -1, 2-diphynel-ethanone oxime [H2L] and KOH with ( Mn II, Fe II, Co II, Ni II , Cu II and Hg II ), in methanol with (2:1) metal: ligand ratio. The general formula for Cu II and Mn II complexes are [M (HL) 2 Cl.H2O] K, for Co II [Co (HL) 2. H2O] and [M (HL) 2] for the rest of complexes. All compounds were characterised by spectroscopic methods, I.R, U.V-Vis, H.P.L.C, atomic absorption and conductivity measurements chloride content. From the data of these measurements, the proposed molecular structures for Fe II and Hg II complexes are tetrahedrals, while Mn II and Cu II complexes are octahedrals, Ni II complex adopting square planar structure and the complex of Co II ion showed a bipyramidal structure